The Effect of Product Quality and Service Quality on Repurchasing Intention - Erwin Fiki Rizki; Ratih Juliati; Ardik Praharjo (Jurnal Manajemen Bisnis dan Kewirausahaan (JAMANIKA), 2021)
This study aims to examine and analyze the effect of product quality on repurchase intention, service quality on repurchase intention at Café Pesenkopi Malang. The population in this study were all consumers who had bought at a coffee shop using samples is 100 consumers. The sampling technique used snowball sampling and the data collection technique used an online questionnaire through social media. The analysis tool uses Smart PLS 3.0. The results of this study indicate that there is a positive and significant effect of product quality on repurchase intention, and service quality on repurchase intention. The dominant variable on consumer repurchase intention is product quality.